Association between control status of blood pressure and frailty among middle-aged and older adults with hypertension in China: a longitudinal study. Issue 3 (14th March 2022) - Shen, Feifei; Chen, Jiangyun; Yang, Ruijing; Yang, Jun; Li, Haomiao
Abstract : Objective: To assess the association between blood pressure (BP) control and frailty among middle-aged and older populations with hypertension in China from 2013 to 2018. Design: Prospective longitudinal study. Setting: This study analysed data from the China Health and Retirement Longitudinal Study, a nationally representative survey administered in 28 provinces of China. Participants: A total of 3254 participants diagnosed with hypertension previous to 2013 were taken into analysis. 1932 participants who were not frail in 2013 were enrolled to calculate relative risk. Outcome measures: The frailty score was constructed following Rookwood's Cumulative deficit frailty index, with a score >0.25 defined as frailty (outcome variable). The self-reported status of BP control (exposure variable) represented the general status of the participant's BP level. A fixed-effects model was used to analyse the association between BP control and frailty. A Cox proportional hazard model was further used to further calculate the relative risk of frailty for different BP control levels. Results: The fixed-effects model showed that compared with well-controlled BP, poorly controlled BP exhibited a positive association with frailty score (β=0.015; 95% CI 0.011 to 0.019; p<0.001). The Cox proportional hazard model also revealed a higher risk of frailty in the poorly controlled group (HR=1.96; 95% CI 1.49 to 2.56; p<0.001). Based on subgroup analyses, poorly controlled BP was positively associated with frailty in respondents aged <60 years old (fix-effects model: β=0.015, p=0.021; Cox model: HR=2.25, p<0.001), but not significant among those aged ≥75 years old. Conclusions: We provide new evidence of a negative association between BP control and frailty risk, but the findings differ among different age groups. Individualised strategies for BP management should be developed, especially for older hypertension patients.